THEORETICAL RECONSTRUCTION OF GLOBAL CURRICULUM DEVELOPMENT: A COMPARATIVE ANALYSIS OF THE THOUGHT OF IBN KHALDUN AND JOHANN HERBART - Itsna Rusydiana (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study aims to reconstruct the theoretical foundation of global curriculum development through a comparative analysis of Ibn Khaldun’s and Johann Friedrich Herbart’s educational thought. Educational transformation in the era of globalization has strengthened technocratic paradigms emphasizing standardization and performativity, often marginalizing the social and moral dimensions of curriculum. This research employs a qualitative philosophical approach using a comparative philosophical inquiry design. Data were obtained through hermeneutic analysis of the primary works of both scholars and relevant supporting literature. The findings reveal that Ibn Khaldun emphasizes the socio-contextual dimension of education as part of civilizational dynamics, while Herbart highlights systematic pedagogy and the moral formation of individuals. Their synthesis generates an integrative conceptual model of global curriculum based on three dimensions: socio-contextual, systematic-pedagogical, and ethical-democratic. This model offers an alternative to technocratic reductionism by positioning curriculum as a dialogical space between social solidarity and moral autonomy. Consequently, global curriculum development should aim to cultivate intellectually competent individuals who possess social awareness and ethical integrity within an increasingly plural and interconnected world.